NEW STONE RELIEFS FROM KUBACHI – ARCHITECTURAL DETAILS OF THE 14TH–15TH CENTURIES WITH GRAPHIC SUBJECTS - Маммаев, Мисрихан Мамаевич (History, Archeology and Ethnography of the Caucasus, 2020)
The article introduces new stone reliefs – details of architectural décor of the 14th–15th centuries with a graphic narrative. The reliefs were discovered by the author in the village of Kubachi in different years of the 20th century, and only now gained special attention.The reliefs in question are scattered through various buildings of the old part of the village, mainly in its middle and lower districts.The integrity of the reliefs varies: some remained in a good state, some – in fragments, others – in poor condition.In most cases, it was not possible to photograph them from the desired angle due to their inaccessibility (second or third floors of buildings in very densely built-up areas, etc.).Most of the reliefs date back to the 14–15th centuries. The dating was carried out according to stylistic features, taking into consideration the fact that a huge number of stone reliefs with graphical subjects were made in Kubachi in the said time period. These reliefs are now stored in many domestic and foreign museums and have partially preserved in Kubachi.The description of the reliefs is given in the order of their record by the author at different times and in different districts of the village.
Keywords: Дагестан; с. Кубачи; каменные рельефы – архитектурные детали; XIV–XV вв.; изобразительные сюжеты; вторичное использование рельефов в декоративных целях.